The Position Study of Heavy Reduction Process for Improving Centerline Segregation or Porosity With Extra‐Thickness Slabs. Issue 4 (28th October 2013) - Zhao, Xinkai; Zhang, Jiongming; Lei, Shaowu; Wang, Yuanning
<x xml:space="preserve">Abstract</x> Limited by reduction radio, heavy plates manufactured from slabs are always subjected to deterioration of soundness and mechanical properties. For overcoming these defects, in the current works, a new approach, named heavy reduction process to improve segregation and porosity, was presented. The aim this study was to fix the dividing position of improving centerline segregation or porosity. Based on the world's maximum thickness vertical‐bending type caster, a two‐step strategy was preceded using software THERCAST, which was coupled macroscopic segregation with thermal‐mechanical GNS method firstly. According to the real production condition of superheat, casting speed and spray intensity, the depth of mushy zone and the terminal end of solidification in width direction were modeled. After this, the distribution of pressure and bulging were presented, and four positions were preliminarily determined based on the curves. Finally, the element concentration, cracks and reduction rate at these different reduction positions were discussed further. The results indicate that the division point of improving centerline segregation or porosity is confirmed ultimately.